O ATO DE JULGAR E O CONFLITO A PARTIR DE RICOEUR - PEREIRA, Luciana da Luz (2023)
ABSTRACT. The aim of this dissertation is to analyze the philosophical relationship between the act of judging and violence in the legal and political scope from Paul Ricoeur. In this way, we demonstrate, at first, the ethical-moral bases of Ricoeur theory of justice, seeking to understand, then, the act of judging through law as a kind of non- violence. The act of judging establishes the mediation of the “third party”, the instance capable of arbitrating the conflict to the detriment of the possibility of taking justice into one's own hands. This instance elevates the conflict to the field of language, contributing to social peace. The “magistrate”, despite the legitimate violence of the state, performs a kind of non-violence, through the exercise of the word in the courts. Based on this issue of non-violence, we reflect on the possibility of articulation between the legal and political spheres, considering the state's relationship with violence and the strategies of the prophetic act, of active non-violence in the face of an unjust state. In this sense, the work accompanies these two spheres: the act of judging and the prophetic act in order to think of two forms of non-violence and two ways of promoting public peace. We believe that the act of judging and the prophetic act can provide an antidote, albeit fragile, for the realization of public peace. Injustice and violence can rule both the field of law (legal) and the field of the state. The courts are linked to a state, which uses legitimate violence, an unjust state can be the holder of unjust institutions and the rule of law can become an ideological apparatus of this same state. In this sense, we debate the alternative of civil disobedience and the strategy of active non-violence, insofar as political non-violence is a reaction to history that is violence. The present investigation seeks to measure the scope of the legal sphere as contributions to public peace in the legal field, for which it takes up the problem of Ricoeur theory of justice, at the same time that it advances to the field of politics. Thus, an attempt is made to intertwine Ricoeur legal debate, from his last phase, with some of his contributions on the political debate of the fifties and sixties.